Postmortem imaging as a complementary tool for the investigation of cardiac death - Katarzyna Michaud; Pia Genet; Sara Sabatasso; Silke Grabherr (Oxford University Press, 2019)
In the past 2 decades, modern radiological methods, such as multiple detector computed tomography (MDCT), MDCT-angiography, and cardiac magnetic resonance imaging (MRI) were introduced into postmortem practice for investigation of sudden death (SD), including cases of sudden cardiac death (SCD). In forensic cases, the underlying cause of SD is most frequently cardiovascular with coronary atherosclerotic disease as the leading cause. There are many controversies about the role of postmortem imaging in establishing the cause of death and especially the value of minimally invasive autopsy techniques. This paper discusses the state of the art for postmortem radiological evaluation of the heart compared to classical postmortem examination, especially in cases of SCD. In SCD cases, postmortem CT is helpful to estimate the heart size and to visualize haemopericardium and calcified plaques and valves, as well as to identify and locate cardiovascular devices. Angiographic methods are useful to provide a detailed view of the coronary arteries and to analyse them, especially regarding the extent and location of stenosis and obstruction. In postsurgical cases, it allows verification and documentation of the patency of stents and bypass grafts before opening the body. Postmortem MRI is used to investigate soft tissues such as the myocardium, but images are susceptible to postmortem changes and further work is necessary to increase the understanding of these radiological aspects, especially of the ischemic myocardium. In postsurgery cases, the value of postmortem imaging of the heart is reportedly for the diagnostic and documentation purposes. The implementation of new imaging methods into routine postmortem practice is challenging, as it requires not only an investment in equipment but, more importantly, investment in the expertise of interpreting the images. Once those requirements are implemented, however, they bring great advantages in investigating cases of SCD, as they allow documentation of the body, orientation of sampling for further analyses and gathering of other information that cannot be obtained by conventional autopsy such as a complete visualization of the vascular system using postmortem angiography.Key points There are no established guidelines for the interpretation of postmortem imaging examination of the heart At present, postmortem imaging methods are considered as less accurate than the autopsy for cardiac deaths Postmortem imaging is useful as a complementary tool for cardiac deaths There is still a need to validate postmortem imaging in cardiac deaths by comparing with autopsy findings